Differences of Circulating Inflammatory Markers between Large- and Small Vessel Disease in Patients with Acute Ischemic Stroke - Zeng, Lili (Ivyspring International Publisher, 2013)
Background: The difference of inflammatory response between the pathogenesis of cerebral large- and small vessel disease after stroke remains unclear. In present study, we aim to determine the association of circulating inflammatory markers with different stroke subtype. Methods: 99 patients with non-cardioembolic stroke were divided into large artery atherosclerosis (LAA) and small-artery occlusion (SAO) according to TOAST classification. A panel of plasma inflammatory markers including leukocyte, lymphocyte, CRP, fibrinogen, D-dimer, CD40L, IFN-γ, IL-1α, IL-1β, IL-6, IL-8, IL-17 and TNF-α were measured within 72 hours following cerebral ischemia. The relation of their levels in plasma with stroke subtype was further studied. All statistical data analysis was performed by SPSS 17.0 software. Results: We found that only CRP were closely associated with stroke subtype (p<0.05). Compared to SAO subgroup, the plasma levels of CRP was higher in LAA subgroup (p<0.05). The predictive efficiency of CRP more than 3.2 for LAA was 85.7% sensitivity. The influencing factor of CRP includes IL-6, lymphocyte, fibrinogen and D-dimer. Conclusion: LAA had a stronger activation of inflammation than SAO in the pathogenesis, which was associated with the changes of CRP.